AMPHIBIANS - Indraneil, Das; Ramlah, Zainudin; Pui Yong, Min; Elvy Quatrin, Deka; Taha, Wahab (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
The amphibian fauna of Bako National Park remains poorly known, compared to the more accessible protected areas of western Sarawak, such as Kubah, Gunung Gading or Gunung Santubong. Contributing factors include the relatively complicated access, requiring a road — and then, a boat-journey, a relative shortage of bodies of freshwater, particularly, large rivers and of high hills. Nonetheless, as of August 2022, a total of 26 species of amphibians have been recorded from the Park (see Checklist). The fauna comprises four bufonids, five dicroglossids, two megophryids, five microhylids, five ranids and five rhacophorids. Of these, nine species are Bornean endemics.